Exploring consumer demand for organic vegetables in Davao City - Deña, Cristina Y.
Organic agriculture is a system that eliminates the used of synthetic inputs and replaced with site-specific management practices that maintain and increase soil fertility. It refers also to the production systems that are formally guaranteed as ?organic? following internationally accepted certification standards. Demand for organic vegetables is increasing worldwide,because of the growing awareness about the benefits that one can get consuming organic vegetables. In Davao City,massive promotions were undertaken by local governments for farmers to shift into organic farming. However,farmers were discouraged to shift into organic farming because of the uncertainty with the demand for organic vegetables. Thus,this study was conducted to explore consumer demand for organic vegetables in Davao City. The study employed cross tabulation analysis to know the relationship of respondents' socio-economic and demographic profile with their awareness level,consumption and purchase pattern as well as their willingness to pay for organic vegetables. Also,factor analysis was employed to know the factors that affect the perception if the respondents regarding organic vegetables. Results showed that respondents were aware about organic vegetables because they heard it. Majority of them have consumed and bought organic vegetables. Respondents were willing to pay a price premium of 10% to 15% for organic vegetables. Respondents perceived organic vegetables as good vegetables,expensive,but wilt faster. The study concludes that there is demand for organic vegetables in Davao City. However,it is still immature stage thus;increasing awareness for the value of organic vegetables is of great importance for the expansion of organic agriculture in Davao City.